The first reptilian allergen and major allergen for fish‐allergic patients: Crocodile β‐parvalbumin. Issue 5 (13th May 2022) - Ruethers, Thimo; Nugraha, Roni; Taki, Aya C.; O'Malley, Andrea; Karnaneedi, Shaymaviswanathan; Zhang, Stephanie; Kapingidza, A. Brenda; Mehr, Sam; Kamath, Sandip D.; Chruszcz, Maksymilian; Mackay, Graham; Campbell, Dianne E.; et al.
Abstract: Background: Clinical cross‐reactivity between bony fish, cartilaginous fish, frog, and chicken muscle has previously been demonstrated in fish‐allergic patients. In indicative studies, two reports of anaphylaxis following the consumption of crocodile meat and IgE‐cross‐binding were linked to the major fish allergen parvalbumin (PV). This study investigates IgE‐binding proteins in crocodile meat with a focus on PV and their clinical relevance. Methods: Proteins were extracted from muscle tissue of crocodile, three bony fish, and two cartilaginous fish. A cohort of fish‐allergic pediatric patients ( n = 77) underwent allergen skin prick testing (SPT) to three fish preparations ( n = 77) and crocodile ( n = 12). IgE‐binding proteins were identified and quantified by SDS‐PAGE, mass spectrometric analyses, and immunoblotting using commercial and in‐house antibodies, as well as individual and pooled patients' serum. PV isoforms were purified or recombinantly expressed before immunological analyses, including human mast cell degranulation assay. Results: Of the tissues analyzed, PV was most abundant in heated crocodile preparation, triggering an SPT of ≥3 mm in 8 of 12 (67%) fish‐allergic patients. Seventy percent (31 of 44) of fish PV‐sensitized patients demonstrated IgE‐binding to crocodile PV. Crocodile β‐PV was the major IgE‐binding protein but 20‐fold less abundant than α‐PV. Cellular reactivity was demonstrated for β‐PV and epitopes predicted, explaining frequent IgE‐cross‐binding of β‐PVs. Both PV isoforms are now registered as the first reptile allergens with the WHO/IUIS (β‐PV as Cro p 1 and α‐PV as Cro p 2). Conclusion: Fish‐allergic individuals may be at risk of an allergy to crocodile and should seek specialist advice before consuming crocodilian meat.